2021
DOI: 10.3389/fmicb.2021.735732
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Ability and Mechanism of a Broad-Spectrum Antifungal Strain Bacillus safensis sp. QN1NO-4 Against Strawberry Anthracnose Caused by Colletotrichum fragariae

Abstract: Strawberry is a very popular fruit with a special taste, color, and nutritional value. Anthracnose caused by Colletotrichum fragariae severely limits fruit shelf life during post-harvest storage. Use of traditional chemical fungicides leads to serious environment pollution and threatens food safety. Biocontrol is considered as a promising strategy to manage the post-harvest fruit diseases. Here, strain QN1NO-4 isolated from noni (Morinda citrifolia L.) fruit exhibited a high antifungal activity against C. frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 64 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…Studies on combined, possibly synergistic actions are in progress. The compelling antagonistic capacities of B. velezensis BA3 and BA4 agree with a number of literature reports focusing on biocontrol capabilities of species belonging to the genus Bacillus , which excel in their ability to produce a wide range of bioactive antimicrobial substances such as lipopeptides, antibiotics, enzymes, polyketides, and non-ribosomal proteins [ 36 , 41 , 42 , 43 ]. Since the members of the genus are characterized by their ability to produce heat, drought, and solvent-tolerant endospores, they are, with respect to durability, almost ideally suited for their inclusion in biocontrol formulations [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies on combined, possibly synergistic actions are in progress. The compelling antagonistic capacities of B. velezensis BA3 and BA4 agree with a number of literature reports focusing on biocontrol capabilities of species belonging to the genus Bacillus , which excel in their ability to produce a wide range of bioactive antimicrobial substances such as lipopeptides, antibiotics, enzymes, polyketides, and non-ribosomal proteins [ 36 , 41 , 42 , 43 ]. Since the members of the genus are characterized by their ability to produce heat, drought, and solvent-tolerant endospores, they are, with respect to durability, almost ideally suited for their inclusion in biocontrol formulations [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 84%
“…The dual culture assay in our study again proved successful as a valuable qualitative approach to quickly assess antagonistic activities of microorganisms directed at fungal postharvest phytopathogens [ 25 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the efficacy of fermentation broth of Streptomyce F2 on inhibiting the growth of anthracnose fungus of peppers was decreased at temperatures above 70°C ( Jiang and Song, 2015 ). In addition, the biocontrol activity of fermentation extract of Streptomyce H4 was maintained under ultraviolet light and strong alkaline conditions but was decreased under high temperatures and strong acid conditions ( Li et al, 2021a , b ). Unlike these previous findings, our study revealed that the fermentation extract of biocontrol strain STR-1 maintained high antifungal activity at temperatures ranging from 40°C to 130°C and exhibited stability within the pH range of 2.0 to 12.0 ( Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds inhibit the synthesis of functional proteins by down-regulating specific functional protein coding genes [31,57,58]. 2,5-Piperazinedione, 3-methyl-6-(1-methylethyl)-and 2,5-Piperazinedione, 3,6-bis(2-methylpropyl)are found in many strains of Bacillus and have been reported to exhibit strong antifungal activity against various phytopathogenic fungi [31,[59][60][61][62]. Additionally, 9-octadecenamide, (Z) has also been reported to possess antimicrobial properties [63,64].…”
Section: Discussionmentioning
confidence: 99%